PENGARUH AEROBIC LOW IMPACT TERHADAP KUALITAS TIDUR PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA BUDI MULIA 4 CIRACAS JAKARTA TIMUR - Agustina, Dwi; Sigrowati, Wahyu; Ali, Mohammad (JURNAL PROFESIONAL FISIOTERAPI, 2025)
Introduction: Sleep problems are increasing in the elderly, with approximately 60% of elderly in Indonesia experiencing them. Sleep disorders can impact daily activities and increase the risk of chronic diseases such as cardiovascular disease, type 2 diabetes, and obesity. Non-pharmacological therapies such as low-impact aerobics were chosen because they can stimulate the production of serotonin and melatonin, which regulate circadian rhythms. Methods: This study used a quasi-experimental design with a pretest-posttest with a control group. A total of 24 elderly were selected purposively and divided into two groups: 12 in the treatment group and 12 in the control group. The low-impact aerobic intervention was carried out 3 times a week for 4 weeks. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Results: There was a significant increase in the mean sleep quality in the treatment group (mean score from 14.00 to 7.33; p=0.0001), while the control group experienced a non-significant decrease (12.33 to 13.00; p=0.071). There was a significant difference in the mean sleep quality between groups (-5.67, p=0.0001). Conclusion: Low-impact aerobics effectively improves sleep quality in the elderly and can therefore be used as an alternative to physiotherapy interventions.